PENGARUH RIGHT ISSUE TERHADAP TINGKAT KEUNTUNGAN DAN LIKUIDITAS SAHAM EMITEN DI BURSA EFEK JAKARTA - Dedi Rusdi; Angga Avianto (Majalah Ilmiah Sultan Agung, 2009)
The efficient market hypotheses state that security prices intaneously reflect all relevant available information. The purpose of this study is to investigate the investor reaction is proxied by abnormal return surrounding announcement day. The sample are the right issue by firms listed in Jakarta Stock Exchange during the period 2003-2007. Event study with 11 event window (from day -5 to day +5) is used to investigate the investors reaction. Abnormal return was calculated by market model. Generally, we find that there is not any different stock return significantly, either before, after, or arround right issue announcement, this means that right issue does not have an information content. There is no change of stock return, caused by possibility of insider information which received by investor or there is another information that is more important than right issue announcement. In 2003-2007, the condition ofÂ Jakarta Stock Exchange did not include a semi market efficiency.Finally, we conclude that right issue announcement was not a good news for investor, the information of right issue hasnâ€™t been received together by investor yet.Kata kunci : Right issue, profit , liquidity stock